Imbalance of thalamic metabolites in an experimental model of hypertension: role of bergamot polyphenols - Carresi, Cristina; Cardamone, Antonio; Coppoletta, Anna Rita; Mollace, Annachiara; Musolino, Vincenzo; Gliozzi, Micaela; Mollace, Vincenzo (Frontiers in Integrative Neuroscience, 2023)
Cerebral metabolites are associated with different physiological and pathological processes in brain tissue. Among them, theC concentrations of N-acetylaspartate (NAA) and choline-containing compounds (Cho) in the thalamic region are recognized and analysed as important predictiveor markers of brain impairment. The relationship among hypertension, modulation of brain metabolite levels and cerebral diseases is of recent investigation, leaving many unanswered questions regarding the origin and consequences of the metabolic damage caused in grey and white matter during hypertension. Here we provide evidence for the influence of hypertension on NAA and Cho ratios in hypertensive rat thalamus and how the use of natural occurring compounds ameliorates the balance of thalamic metabolites.